A Simple Technique for Rapid Assessment of Rat (Rattus norvegicus) Sperm Motility - Muhammad Ja'far Luthfi; Mahanem Mat Noor (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2020)
Assesment of rat sperm motility can be carried out on sperm sample from epididimal source using minimal amount of equipment. This method will aid researcher and practitioner working in the field of sperm quality to determined rat sperm motility rapidly and efficiently.